Impact of Corporate Social Responsibility on a Private Limited Company. - Akash Negandhi, Shelina Dharani (International Journal of Advanced Science and Technology, 2020)
The purpose of this investigation was to find out the overall impact that corporate social responsibility has had on Frazs Industries Limited. This investigation focused on both primary and secondary data that was collected from the organisation. The primary data that was collected during the investigation was to see how the adoption of a new practice has influenced everybody’s mind set who works as part of the organisation and the secondary data collected which included the record of absent employees, employees that have left the business, changes in the quantity of lead that the business recycles and income statements played a major role in identifying the new trends that this practice brought up. While CSR was mainly addressed from the perspective of larger enterprises, it is also a process for boosting private company’s competitiveness (Szabo, 2008:17). There are fundamental responsibility issues to be tackled by all companies, regardless of scale, such as maintaining a healthy working atmosphere in which diversity is promoted, an equal distribution of resource in a society, environmental security, technological developments and rightful practices (Jenkins, 2006b:2; European Competitiveness Report, 2008:119). In conclusion it was seen that even though the adoption of Corporate Social Responsibility (CSR) has increased the costs of the business it has enabled the business to achieve certain things in different aspects of the business which would not have been possible without the adoption of Corporate Social Responsibility. Therefore, the practice of being socially responsible was taken to be beneficial for the business and considered to be creating a positive impact on the business.